DINAMIKA HALAQAH DI ERA MEDIA SOSIAL: STUDI HISTORIS METODE TRANSMISI KEILMUAN ISLAM - Fadhli Alfayyadh; Noval Khairul Ihsan; Muhammad Syari Arip; Herlini Puspika Sari (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
Islamic education is currently facing inevitable digital disruption, shifting the method of transmitting knowledge from traditional halaqah to virtual halaqah on social media. This study aims to analyze the historical role of halaqah, describe the dynamics of its shift in the social media era, and formulate a synthesis of the integration of its historical values ​​into the digital ecosystem. Using a qualitative approach through historical and library studies, data was collected and analyzed descriptively and analytically. The results show that the transformation of learning spaces from mosques to social media does provide very broad accessibility, but also triggers democratization that leads to the fragmentation of religious authority, problems with the validity of scientific chains of transmission, and shallowing of understanding due to content simplification. In conclusion, the dynamics of digital halaqah represent an inevitable form of methodological evolution. As a consequence, Islamic educational institutions need to formulate a hybrid halaqah curriculum that combines the efficiency of digital technology with the sharpness of traditional talaqqi methods, and strengthen digital literacy to maintain the essence of moral formation.